Study on cooperative constraint zoning of water environment. (3rd September 2022) - Liu, Lanxin; Li, Zhidong; Zhao, Penglei; Leng, Xuefei
Abstract: This study comprehensively considers two elements of water environmental sensitivity and pressure using the combination of qualitative analysis and quantitative calculation. And it puts forward the water environmental collaborative constraint zoning method and focuses on the construction of the water environmental collaborative constraint zoning evaluation index system using the fuzzy optimization programming model to determine the index weight. This study takes the Liaohe River Basin in Liaoning Province as a study area through two-dimensional quadrant analysis of water environmental sensitivity and pressure; it is divided into four types of areas: high-pressure and high-sensitivity area (HP-HS area), high-pressure and low-sensitivity area (HP-LS area), low-pressure and high-sensitivity area (LP-HS area) and low-pressure and low-sensitivity area (LP-LS area), respectively. The results show that the proportion of HP-HS area is 28.4%, the proportion of HP-LS area is 10.1%, the proportion of LP-HS area is 22.2% and the proportion of LP-LS area is 39.3%, respectively. The evaluation results are in line with the actual situation of the Liaohe River Basin in Liaoning Province. According to the results of different zoning, this research puts forward the optimization and adjustment scheme of industrial layout to achieve the comprehensive and coordinated sustainable development of population, economy, society, and environment in the study area. The research results also have been applied to the formulation of '14th Five-Year Plan' for water ecological environment protection of key river basins in Liaoning Province. HIGHLIGHTS: This paper comprehensively considers the two elements of water environment sensitivity and pressure, puts forward the zoning method of water environment collaborative constraints, adopts the combination of qualitative analysis and quantitative calculation, focuses on the construction of the evaluation index system of water environment collaborative constraints. Graphical Abstract